High gene flow promotes the genetic homogeneity of the fish goby Pomatoschistus marmoratus (Risso, 1810) from Mar Menor coastal lagoon and adjacent marine waters (Spain) - Vergara-Chen, Carlos (2017)
The extreme environmental variability of coastal lagoons suggests that physical and ecological factors could contribute to the genetic divergence among populations occurring in lagoon and open-coast environments. In this study we analysed the genetic variability of lagoon and marine samples of the sand goby, Pomatoschistus marmoratus (Risso, 1810) (Pisces: Gobiidae), on the SW Spain coast. A fragment of mitochondrial DNA control region (570 bp) was sequenced for 196 individuals collected in five localities: Lo Pagan, Los Urrutias and Playa Honda (Mar Menor coastal lagoon), and Veneziola and Mazarro´n (Mediterranean Sea). The total haplotype diversity was h = 0.9424 ± 0.0229, and the total nucleotide diversity was p = 0.0108 ± 0.0058. Among-sample genetic differentiation was not significant and small-scale patterns in the distribution of haplotypes were not apparent. Gene flow and dispersal-related life history traits may account for low genetic structure at a small spatial scale. The high genetic diversity found in P. marmoratus increases its potential to adapt to changing conditions of the Mar Menor coastal lagoon.